2010
DOI: 10.1051/ocl.2010.0286
|View full text |Cite
|
Sign up to set email alerts
|

Thanks to literature and fellow scientists

Abstract: Formal training has the disadvantage that trainees may simply accept what they are taught without questioning it, unlike the autodidact who can only learn by asking questions all the time. Sometimes, he will not get an answer and that need not be because the question is stupid, but may be because his peers are used to there being no satisfactory answer and have simply accepted the conventional mythology without further question. So it is about time to ask some assorted questions and where possible, suggest how… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
5
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 26 publications
0
5
0
Order By: Relevance
“…He also found that monounsaturated fatty acids were almost insusceptible to oxidation, while linoleic acid and linolenic acid were extremely susceptible. His research was all carried out at 120 °C with an automatic Rancimat apparatus, which was close to theoretical autoxidation experimental conditions. Different from his research, our research was conducted under real frying conditions at 180 °C, which was very close to the actual frying process in life.…”
mentioning
confidence: 78%
See 1 more Smart Citation
“…He also found that monounsaturated fatty acids were almost insusceptible to oxidation, while linoleic acid and linolenic acid were extremely susceptible. His research was all carried out at 120 °C with an automatic Rancimat apparatus, which was close to theoretical autoxidation experimental conditions. Different from his research, our research was conducted under real frying conditions at 180 °C, which was very close to the actual frying process in life.…”
mentioning
confidence: 78%
“…By carefully reading the introduction and the original text of the previously published article mentioned in the Letter, we knew that Dr. Albert Dijkstra had done a lot of research on the oil stability index (OSI). He found that the OSI of oil blends can be expressed as the sum of the antioxidant contents of the blend components divided by the sum of the weighted susceptibilities to the oxidation of the fatty acids in the blend.…”
mentioning
confidence: 99%
“…Hence, the continuous efforts to discover why oils are so unstable, how different oils compare and what to do about it. So, when I was still in charge of an R&D laboratory we also studied oil stability and we even published the results . We used the Rancimat apparatus to determine the Oil Stability Index (OSI) and by testing a large number of binary blends of twenty vegetable oils and fats, we concluded that this index can be predicted on the basis of the antioxidant content of the oils and constituting the blend and the fatty acid composition of the blend according to: R=truenormalixiaitruenormaljyjvj …”
Section: Introduction and Some Observationsmentioning
confidence: 99%
“…It is therefore with great interest that I studied the article by Liu et al because it claims to provide a novel evaluation index for frying oils that only takes their fatty acid composition into account. Another reason that I studied the article with great interest is that some 20‐odd years ago, I wrote a paper that also correlates the stability of an oil to its fatty acid composition. The difference between the work by Liu et al.…”
mentioning
confidence: 99%
“…Because the paper I wrote is not that readily accessible since it dates from before 2000—the year in which Oléagineux, Corps gras, Lipides, the French oils and fats journal (OCL)‐back issues became freely accessible via the Internet—I will briefly summarise its findings. These include that the Oil Stability Index (OSI) of oil blends can be expressed as the sum of the antioxidant contents of the blend components divided by the sum of the weighted susceptibilities to oxidation of the fatty acids in the blend.…”
mentioning
confidence: 99%